Role of Salsylic Acid, Fertilizer NPKzn and Sodium Chloride and Theris interactions in Some Morphological Parameters of Allium cepa L. - S. Hassan, May; J. Al- Saedi, Abbas (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The experiment was condncted in greenhouse of Botanical Garden at Biology Garden Dept,College of Education for Pure Science (Ibn-Al-Haitham),University of Baghdad , during the growing season  2013-2014 to study the role of salcylic acid in three concentrations (0.12and24) ppm and two levels of NPKZn fertilizer ( 0. 160) kg.Hâ€¾1 and four concentrations of sodium chloride (0.50.100and150) Mmol and the intreaction between salcylic acid and NPKZn on some of morphological parameters of Allium cepa.                                 The experiment was performed with random compelete block design (RCBD)with three replications and the results showed the following                                                         1-The sparying of salcylic acid led to aignificant increase in all parameters compared with control treatment              .                         2-Treatment with two levels of NPKZn fertilizer caused a significant increase in all    parameters                                                                                                                                      3-The interaction between salcylic acid and NPKZn fertilizer led to increase all parameters and the treated plants with 24 ppm showed the highest influence.